2019
DOI: 10.1093/cercor/bhz285
|View full text |Cite
|
Sign up to set email alerts
|

Associating Psychotic Symptoms with Altered Brain Anatomy in Psychotic Disorders Using Multidimensional Item Response Theory Models

Abstract: Reduced cortical thickness has been demonstrated in psychotic disorders, but its relationship to clinical symptoms has not been established. We aimed to identify the regions throughout neocortex where clinical psychosis manifestations correlate with cortical thickness. Rather than perform a traditional correlation analysis using total scores on psychiatric rating scales, we applied multidimensional item response theory to identify a profile of psychotic symptoms that was related to a region where cortical thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…When comparing our results to previous dimensional studies, a recent study also identified subcortical volume reductions associated with hallucinations as well as delusions [ 69 ], but reductions of superior temporal areas have also been well established in SSD [ 1 , 3 , 70 , 71 ]. The present findings are also in line with a recent investigation where psychotic symptoms were negatively correlated with CT in a large sample of SSD patients, relatives and healthy controls [ 72 ]. Consistent with previous studies in SSD, we found cortical thinning in the bilateral STG to be correlated with the PHS factor [ 73 ], indicating this brain structure to be a core feature of positive symptomatology.…”
Section: Discussionsupporting
confidence: 93%
“…When comparing our results to previous dimensional studies, a recent study also identified subcortical volume reductions associated with hallucinations as well as delusions [ 69 ], but reductions of superior temporal areas have also been well established in SSD [ 1 , 3 , 70 , 71 ]. The present findings are also in line with a recent investigation where psychotic symptoms were negatively correlated with CT in a large sample of SSD patients, relatives and healthy controls [ 72 ]. Consistent with previous studies in SSD, we found cortical thinning in the bilateral STG to be correlated with the PHS factor [ 73 ], indicating this brain structure to be a core feature of positive symptomatology.…”
Section: Discussionsupporting
confidence: 93%
“…This relaxes the assumption of an interval scale of measurement such that every additional unit/interval increase of the SVM score does not have to reflect a uniform magnitude of increased/decreased social vulnerability. While many of the SDoH variables are measured on a continuous scale, we transformed them to quintiles for analysis and scoring, similar to previous methods applying the bifactor model to a mix of clinical and biological variables 19 . The scores for the primary dimension of SDoH are Bayes expected a posteriori (EAP) estimates that are expressed on an underlying unit normal (N(0,1)) scale and can be transformed to percentiles using an inverse normal transformation.…”
Section: Methodsmentioning
confidence: 99%
“…While many of the SDoH variables are measured on a continuous scale, we transformed them to quintiles for analysis and scoring, similar to previous methods applying the bifactor model to a mix of clinical and biological variables. 19 The scores for the primary dimension of SDoH are Bayes expected a posteriori (EAP) estimates that are expressed on an underlying unit normal (N(0,1)) scale and can be transformed to percentiles using an inverse normal transformation. We computed the empirical reliability of the test as the ratio of the empirical variance of the test (expected value = 1.0, true score variance) to the total variance, or the empirical variance plus the posterior variance of the estimator (error variance).…”
Section: Methodsmentioning
confidence: 99%
“…Ours is an alternative statistical approach to look at the relationship between psychotic symptoms and regional cortical thickness, using MIRT. The MIRT approach examined both symptomatic (psychosis) and biological (cortical thickness) domains simultaneously while maintaining item-level symptom ratings and regional cortical thickness measures as inputs to the model, simultaneously, aiming to enhance precision in characterizing the relationship [36].…”
Section: Anatomic Fingerprint Of Psychosis: Multidimensional Item Res...mentioning
confidence: 99%